Racial Disparities in Hepatitis B Infection in Ohio: Screening and Immunization Are Critical for Early Clinical Management. (October 2013) - Misra, Ranjita; Jiobu, Karen; Zhang, Johnathan; Liu, Qihui; Li, Feng; Kirkpatrick, Robert; Ho, Jason
Objective: Chronic hepatitis B virus (HBV) infection and liver cancer mortality represent a neglected health disparity among Asian Americans. The purposes of this study were to compare the prevalence of hepatitis B among a diverse group of 1311 Ohioans in Franklin County, OH (85% Asians, 7.5% African Americans, and 6.5% whites) and to improve access to care for high-risk Asian adults through advocacy and policy changes. Research Design and Methods: The Asian subgroups comprised of Chinese, Filipino, Asian Indian, Pakistani, Vietnamese, Korean, Laotian, Indonesian, Japanese, Cambodian, Thai, and Malaysian nationalities. The HBV screening was completed at health fairs, restaurants, churches, and temples from 2006 to 2011. Results: The prevalence of HBV infection (9.5% vs 5%) and family history of liver cancer was significantly higher among Asians than other racial ethnic groups ( P = 0.001). Cambodian, Vietnamese, and Chinese participants were disproportionately infected with the virus compared with other Asian subgroups ( P < 0.001). Advocacy and policy changes for resources allowed vaccine-eligible Asians included as "high risk" group to receive free vaccinations at the health department. However, although vouchers were provided to vaccine-eligible Asian adults, compliance in getting vaccinated was very low (11%). Common barriers for compliance were lack of time and knowledge of completing the 3 shot series, low English proficiency, and fear of adverse effects. Conclusions: Outreach education may use community liaisons to improve screenings, education, and vaccination/treatment. A hepatitis free clinic was established in 2009 to provide culturally and linguistically appropriate treatment for low-income Asian Americans in Franklin County, OH.